SYSTEMATIC INVENTORY FOR HERITAGE SHOPHOUSE FACADES IN IPOH, PERAK, MALAYSIA - Wan Ali, Wan Nordiana; Ahmad, A. Ghafar (PLANNING MALAYSIA, 2021)
Nowadays, many heritage shophouses remain intact in major urban areas in Malaysia, including Ipoh, Perak. These architectural assets are significant as they portray the glory and achievements of Ipoh over the centuries. However, some shophouses face inappropriate façade changes due to improper conservation activities performed on the heritage properties. These situations have resulted in the phenomenon of inconsistency elements of building facades. Therefore, this paper focuses on two aspects regarding heritage shophouse facades; first, developing the taxonomy of architectural styles according to the tangible elements, and second, classifying and grading the architectural styles. Then, an inventory form named eFakad was developed as a tool to evaluate 65 shophouses at Jalan Sultan Iskandar, Ipoh. The result shows that 49% of facades are in excellent condition, but the rest of the facades need to be conserved and maintained, particularly roof finishes, windows and doors. By applying eFakad inventory form, the documentation and conservation management of the heritage shophouses can be done systematically. Consequently, the stakeholders will be aware of the main problems faced by the heritage shophouses through the inventory record and appropriate actions can be taken in preserving the integrity of the facades. Additionally, the local authority may use the information to improve the existing conservation guidelines.